Financial cycles and co-movements between the real economy, finance and asset price dynamics in large-scale crises - Maria Teresa Punzi (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2016)
We empirically analyze asset price boom-bust cycles over a long-run period of 1896-2014 for the U.S., the Netherlands, Norway and Sweden. We focus on macro-financial linkages to understand if these are common phenomena during financial crises, or if the linkage was simply amplified during the last financial crisis in 2007. In particular, we ask if economic recessions are usually followed by asset price and credit bursts, and find that housing and stock prices tend to lead real economic activities, while developments in credit and money markets typically lag developments in the real economy. The dynamic of assets' portfolio allocation effects in times of crises has been the same. We also study the cyclical behaviour of real GDP per capita, asset prices (housing or stocks) and lending. In particular, we test for the existence of co-movements with asset prices during periods of crisis. We find that the correlations between real GDP per capita and real housing prices and between lending and real housing prices have increased since World War II, and that the increase is much more pronounced if we compare the Great Recession with the Great Depression. Monetary policy shocks also become more important in explaining the co-movements in the Great Recession, compared with the Great Depression. Furthermore, inflation shocks have played an important role in explaining the correlation between house prices and lending for Scandinavian countries.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: C23; E32; E44; E52; G10; G21; 330; Housing Prices; Stock Prices; Business Cycle; Co-movements; Large-Scale Dataset